Molecular identification of Sarcocystis spp. helped to define the origin of green pythons (Morelia viridis) confiscated in Germany. - Moré, Gastón Andrés (2014)
Sarcocystis spp. represent apicomplexan parasites. They usually have a heteroxenous life cycle. Around 200 species have been described, affecting a wide range of animals worldwide, including reptiles. In recent years, large numbers of reptiles have been imported into Europe as pets and, as a consequence, animal welfare and species protection issues emerged. A sample of pooled feces from four confiscated green pythons (Morelia viridis) containing Sarcocystis spp. sporocysts was investigated. These snakes were imported for the pet trade and declared as being captive-bred. Full length 18S rRNA genes were amplified, cloned into plasmids and sequenced. Two different Sarcocystis spp. sequences were identified and registered as Sarcocystis sp. from M. viridis in GenBank. Both showed a 95?97% sequence identity with the 18S rRNA gene of Sarcocystis singaporensis. Phylogenetic analysis positioned these sequences together with other Sarcocystis spp. from snakesand rodents as definitive and intermediate hosts (IH), respectively. Sequence data and also the results of clinical and parasitological examinations suggest that the snakeswere definitive hosts for Sarcocystis spp. that circulate in wild IH. Thus, it seems unlikely that the infected snakes had been legally bred. Our research shows that information on the infection of snakes with Sarcocystis spp. may be used to assess compliance with regulations on the trade with wildlife species.